Field-based experimental investigation of energy and exergy performances of a novel solar thermal air collector - Rahmat, Muhammad Aqil Afham; Ibrahim, Adnan; Al-Aribe, Khaled M.; Syafiq, Ubaidah; Ishak, Muhammad Amir Aziat; Ud Din, Sahibzada Imad; Mokhtar, Mohamad Arif; Ahmad Ludin, Norasikin; Fazlizan, Ahmad (Nature Research, 2026)
An energy crisis is a significant concern, and solar collectors are among the most efficient energy conversion devices. Inefficient heat transfer is an issue that reduces overall performance. This research investigates the use of hollow semi-stadium fins (HSSF) arranged in a multi-level array with baffles to enhance the system’s overall performance. Outdoor testing was undertaken over three days with varying flow rates of 0.01 kg/s (Day 1), 0.03 kg/s (Day 2), and 0.07 kg/s (Day 3). The study considered the temperature of the solar collector, as well as its energy and exergy performance. The study found a thermal efficiency range of 12.99–71.91% and a maximum value of 71.91% corresponding to an irradiance of 800 W/m2 and a flow value of 0.07 kg/s. The inlet-to-outlet temperature differential peaked at 21.80 °C at 0.01 kg/s. The most excellent exergy efficiency was 17.06% at a flow rate of 0.01 kg/s, with a range of 0.55% to 17.06% for all irradiances and mass flow rates. Performance results were validated using numerical results and earlier research. Larger flow rates increase thermal efficiency but decrease exergy efficiency. The solar collector with HSSF and baffles highlights its energy and exergy enhancements for sustainable energy applications.